2021
DOI: 10.3389/fimmu.2021.664425
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Dimethoxy-6-Methylbenzene-1,3-diol, a Benzenoid From Antrodia cinnamomea, Mitigates Psoriasiform Inflammation by Suppressing MAPK/NF-κB Phosphorylation and GDAP1L1/Drp1 Translocation

Abstract: Antrodia cinnamomea exhibits anti-inflammatory, antioxidant, and immunomodulatory activities. We aimed to explore the antipsoriatic potential of 2,4-dimethoxy-6-methylbenzene-1,3-diol (DMD) derived from A. cinnamomea. The macrophages activated by imiquimod (IMQ) were used as the cell model for examining the anti-inflammatory effect of DMD in vitro. A significantly high inhibition of IL-23 and IL-6 by DMD was observed in THP-1 macrophages and bone marrow-derived mouse macrophages. The conditioned medium of DMD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…To further confirm if the aforementioned influence of CFT073 wt on polarization of macrophages was caused by TcpC, rTcpC was prepared and its effects on macrophage polarization were also examined. In accordance with previous reports [ 27 , 31 , 32 ], LPS + IFN-γ significantly induced the expression of M1 markers CD80 and CD86, and IL-4 treatment promoted the expression of M2 markers CD163 and CD206 in both THP-1 and J774A.1 macrophage cell lines. However, 4 μg/mL rTcpC treatment profoundly attenuated LPS + IFN-γ=induced expression of CD80 and CD86 ( Figure 4 A–D), while promoting CD163 and CD206 expression ( Figure 4 E–H).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To further confirm if the aforementioned influence of CFT073 wt on polarization of macrophages was caused by TcpC, rTcpC was prepared and its effects on macrophage polarization were also examined. In accordance with previous reports [ 27 , 31 , 32 ], LPS + IFN-γ significantly induced the expression of M1 markers CD80 and CD86, and IL-4 treatment promoted the expression of M2 markers CD163 and CD206 in both THP-1 and J774A.1 macrophage cell lines. However, 4 μg/mL rTcpC treatment profoundly attenuated LPS + IFN-γ=induced expression of CD80 and CD86 ( Figure 4 A–D), while promoting CD163 and CD206 expression ( Figure 4 E–H).…”
Section: Resultssupporting
confidence: 93%
“…It was reported that complete polarization of macrophages to the M1 type requires activation of the MAPK and NF-κB signaling pathways [ 19 , 27 , 31 , 61 ], and M2 macrophage polarization requires activation of the STAT signaling pathway [ 62 , 63 ]. To explore the signal transduction pathways underlying the regulatory effects of TcpC on M1/M2 polarization, the influence of TcpC on MAPK/NF-κB and Akt/STAT pathways was examined.…”
Section: Discussionmentioning
confidence: 99%
“…Our CM functional analyses further show that Gm41664 increases CM apoptosis by regulating the novel miR-150/GDAP1L1 axis. GDAP1L1 is conserved in vertebrates and is involved in the mitochondrial fission [ 42 ]. However, nothing is known about the cardiovascular roles and regulatory mechanisms of GDAP1L1.…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioside Induced Differentiation Associated Protein 1 Like 1 (GDAP1L1) is a regulator of mitochondrial fission. Mitochondrial fission is required for maintaining mitochondrial functions including apoptosis [ 42 ]. GDAP1L1 is mainly expressed in the central nervous system [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…While macrophages are shown to have a high TNF expression [ 19 ], the activation of TLRs can trigger the production of TNFα in macrophages [ 20 ]. IL-23, having a crucial role in psoriasis initiation [ 21 ], is capable of evoking IL-6-dependent cytokine release and epidermal thickening [ 22 ]. Furthermore, both TNF-α and IL-6 can induce IL-24 production in psoriasis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%